Change of approach to using intra-aortic balloon counterpulsation in combined cardiac surgery - Z. Z. Nadiradze (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Perioperative acute myocardial dysfunction is an actual problem of cardiac surgery. Rational use of inotropes and mechanical circulatory support in the postoperative period remains a subject of debate. The outcomes of the combined coronary artery bypass grafting and heart valve prosthesis were analyzed in Irkutsk Cardiac Surgery Center after 80 patients were operated on. As a result of the conducted research, authors proposed a method of differentiated approach to the treatment of acute heart failure in the early postoperative period. Failure to escalate therapy beta agonists in the absence of adequate response hemodynamics and the transition to a mechanical circulatory support improves performance of the cardiovascular system and clinical outcomes, reduces hospitalization duration in the department of intensive therapy. The study showed the superiority of an early beginning of an intra-aortic balloon counterpulsation before traditional inotropic therapy in the treatment of postcardiotomy heartfailure at combined cardiac surgery.